Somalia : COVID-19 High Phone Survey Wave 2 Brief - Kotikula, Andy; Pournik, Milad; Yoshimura, Kazusa (World Bank, Washington, DC, 2021)
In January 2021, the second wave of the Somalia high frequency phone survey has been administered, calling 2,811 households to see the impact of Coronavirus disease 2019 (COVID-19) on people’s behavior and livelihood. The first wave has been conducted in June 2020, and compared to that, the adoption of preventive measures such as washing hands and wearing mask was less widespread in the second wave, while over 90 percent of people expressed interest in getting tested and vaccinated. The overall employment rate seems to have improved from the first wave, but still the majority of households (79 percent) reported the further income reduction. Food insecurity has clearly worsened compared to the first wave while government and non-government assistance appears to have reduced greatly since 2020, which strongly suggests the need of further support to the Somalis, especially the most vulnerable groups including internally displaced populations (IDPs) and nomadic households.